Factors affecting wood, energy grass and straw pellet durability – A review. (May 2017) - Whittaker, Carly; Shield, Ian
Abstract: Pellets produced from wood, energy grasses and straw present a higher energy density feedstock than wood chips or bales, and therefore reduce the costs of handling, transport and storage throughout the supply chain. European specifications provide limits to the proportion of fines (particles less than 3.15 mm) allowed in pellets, which refers to the durability of the pellets. Fines have implications for health and safety in supply chains, and cause issues with slag formation in combustion systems. This paper reviews the factors affecting biomass pellet durability. The industrial trade for wood pellets has expanded greatly over the last decade and involves the international trade of tens of million tonnes annually. Due to increasing demands for pellets, there has been growing interest in utilising more varied biomass types. The aim of this review is to examine feedstock qualities and pelleting conditions that produce durable pellets. Pellet durability can be affected by the feedstock characteristics, the moisture content or size reduction during pre-processing, and by pelleting conditions, including the use of binders, feedstock mixes, temperatures or die pressures. Post-production conditions can also affect durability, such as the storage conditions and handling frequency, therefore an understanding of all the factors affecting durability throughout the supply chain is needed in order to prioritise where advances can be made.